1995
DOI: 10.1016/0005-2736(95)80016-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of dioleoyl phosphatidylethanolamine in cationic liposome mediated gene transfer

Abstract: In a reported gene assay, cationic liposomes containing the cationic lipid 3 beta-(N-(N',N'-dimethylaminoethane)carbamoyl)cholesterol (DC-Chol) and a neural phospholipid dioleoylphosphatidylethanolamine (DOPE) showed high transfection activity. DNA/liposome complex which contained low amount of liposomes could bind to the cell surface but failed to transfect the cells. We have designed a two-step protocol to examine this phenomenon in more detail. A431 human cells were incubated on ice (pulse) with DNA complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
459
1
4

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 763 publications
(479 citation statements)
references
References 16 publications
15
459
1
4
Order By: Relevance
“…DOPE, which contains an ethanolamine head group, promotes transfection whereas a similar neutral phospholipid, dioleoylphosphatidylcholine (DOPC), which contains a choline head group, does not. 142,143 A critical factor accounting for this difference in transfection enhancing activity is that DOPE forms nonbilayer lipid structures whereas DOPC does not (Litzinger D and Huang. Biochim Biophys Acta 1992; 1113: 201).…”
Section: Endosomolysismentioning
confidence: 99%
“…DOPE, which contains an ethanolamine head group, promotes transfection whereas a similar neutral phospholipid, dioleoylphosphatidylcholine (DOPC), which contains a choline head group, does not. 142,143 A critical factor accounting for this difference in transfection enhancing activity is that DOPE forms nonbilayer lipid structures whereas DOPC does not (Litzinger D and Huang. Biochim Biophys Acta 1992; 1113: 201).…”
Section: Endosomolysismentioning
confidence: 99%
“…24 The presence of DOPE greatly enhances the transfection efficiency and is thought to be the consequence of the non-bilayer forming properties of this lipid. 26 Several drawbacks of this transfection system have to be noted. (1) The DNA/lipid complexes formed are not stable in the presence of serum, 27 limiting the application of this system in vivo.…”
Section: Nmol) Were Mixed With Increasing Amounts Of Virosomes Contaimentioning
confidence: 99%
“…In most cases, these lipids are mixed with an equimolar amount of a ''helper'' lipid. Most frequently, the neutral lipid DOPE is used, since this is known to enhance transfection efficiency (Felgner et al, 1994;Gao and Huang, 1995;Stegmann and Legendre, 1997;Zhou and Huang, 1994), due to its ability to facilitate the formation of cationic liposomes and to its tendency to form non-bilayer phases that may contribute to the destabilization of the endosomal membrane (Farhood et al, 1995;Felgner et al, 1994;Legendre and Szoka, 1992;Zhou and Huang, 1994). On the other hand, cholesterol (Chol) constitutes another promising ''helper'' lipid, since it has been demonstrated that high levels of transfection can be obtained both in vitro and in vivo, upon its association with a cationic lipid (Crook et al, 1998;Templeton et al, 1997).…”
Section: Introductionmentioning
confidence: 99%